Young-Onset Early Colorectal Cancer Had Similar Relative Survival to but Better Overall Survival Than Conventional Early Colorectal Cancer: A Large Population-Based Study - Chen, Jin-Nan; Zhang, Qing-Wei; Pan, Yuan-Bo; Wang, Qi-Wen; Zhang, Xin-Tian; Li, Xiao-Bo (Frontiers in Oncology, 2020)
Background: There existed limited evidence about prognosis of young-onset early colorectal cancer (ECRC). In the present study, we aimed to compare prognosis between patients with young-onset ECRCs and patients with conventional ECRCs. Method: Patients with surgically resected, histologically diagnosed ECRCs were retrieved from the Surveillance, Epidemiology, and End Results (SEER) database. Young-onset ECRC was defined ECRC occurring in patients aged less than 50 years. 5- year relative survival was calculated at the time of diagnosed year and linear regression was performed to analyze the association between 5-year relative survival and age. The multivariate Cox regression, multivariate competing risk model and propensity score matching (PSM) and univariate analysis weighted by the inverse probability of treatment weight (IPTW) were used to compare overall survival (OS) between young-onset ECRCs and conventional ECRCs. Results:51197 ECRCs were retrieved from SEER database, including 4634 young-onset ECRCs and 46563 conventional ECRCs. 5-year relative survival was found to be moderately associated with different age groups (R=-0.725, P=0.0034). Patients with young-onset ECRCs (96.7%) had similar 5-year relative survival compared with conventional ECRCs (96.3%). However, multivariate Cox regression (HR [hazard ratio], 0.18; 95%CI, 0.16-0.20; P< 0.001) showed better OS in young-onset ECRCs. After PSM, we still found favored prognosis for young-onset ECRCs under univariate Cox regression (HR, 0.18; 95%CI, 0.16-0.21; P< 0.001). Similar results could also be found in the univariate Cox regression weighted by IPTW (HR, 0.17; 95%CI, 0.17-0.18; P< 0.001). Conclusions: Patients with young-onset ECRCs had similar relative survival but better overall survival compared with conventional ECRCs.